2018
DOI: 10.5056/jnm18004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmabiotic Manipulation of the Microbiota in Gastrointestinal Disorders: A Clinical Perspective

Abstract: The advent and widespread availability of high-throughput technology has revolutionized the assessment of the communities of microorganisms that inhabit the gastrointestinal tract––the gut microbiota. As our understanding of the role of the microbiota in health and human disease increases, so also do efforts to prevent and treat disease through the modulation of the microbiota. Several strategies are available to us and range from time honored approaches, such as antibiotics and probiotics, to changes in diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 108 publications
0
11
0
1
Order By: Relevance
“…Significant evidence supports the relationship between the gut microbiome, inflammation, host response, and health (Pedersen et al, 2016;Dinan and Cryan, 2017;Kelly et al, 2017;Giron and Quigley, 2018). Disruption of the microbiome can lead to changes in microbial metabolism and consequently host metabolism (Belizario et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Significant evidence supports the relationship between the gut microbiome, inflammation, host response, and health (Pedersen et al, 2016;Dinan and Cryan, 2017;Kelly et al, 2017;Giron and Quigley, 2018). Disruption of the microbiome can lead to changes in microbial metabolism and consequently host metabolism (Belizario et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…longum 35624 [42], пробиотика, широко используемого в лечении симптомов СРК. При описании полного генома этой бактерии исследователи идентифицировали конкретный кластер генов, который кодировал механизм, необходимый для синтеза экзополисахаридной (EPS) оболочки, которая имеет противовоспалительную активность [43,44]. Другим фундаментальным компонентом нынешнего определения пробиотика является то, что это живой организм [45] и он выживает при транзите через желудочно-кишечный тракт [46].…”
Section: Bifidobacterium Longum Subsp Longum 35624 в лечении сркunclassified
“…It has been suggested that pharmabiotics include pharmaceutical probiotics with specific evidence of generating health benefits and with proven positive physiological effects, or with the capacity to play a pharmacological role in diseases. 15,16 Hence, pharmabiotics comply with two criteria: 16 (a) they provide physiological and pharmacological health benefits against diseases; and (b) they serve as prevention and treatment for medical conditions.…”
Section: Pharmabioticmentioning
confidence: 99%